“THE ROLE OF SIMULATION-BASED LEARNING IN NURSE TRAINING” (The Conference Hub, 2025)
Simulation-based learning is a modern and effective educational method that provides a unique opportunity to practice critically important practical skills in a safe and controlled environment. Research shows that simulation training significantly improves nurses’ skills in resuscitation and emergency care. Through scenario-based learning, students can acquire essential competencies such as interpersonal communication, teamwork, leadership, decision-making, task prioritization under pressure, and stress management.